What's 'Open' about Open Access? The Vital Role of Copyright and Licenses - Prosser, David C. (Septentrio Conference Series, 2014)
See video of the presentation. Access is only half of the Open Access story. A vital component is what you can do with the content that you have access to. Can you use it for teaching and learning in the classroom? Text and data-mine? Create anthologies and reading lists? Archive and preserve the material for future generations? The answers to these questions depend, in part, on the copyright status of the material and the licensing terms under which the material is made available. This paper will investigate the importance of licenses and focus on the 'open' of Open Access.